Review paperVitamin D and its receptor – role and activity in the human body. Anomalies of metabolism and structure associated with psoriasis - Kolanko, Magdalena; Brzezińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Psoriasis is a common, chronic and recurrent inflammatory dermatosis with abnormally exaggerated epidermal cellular turnover, which affects about 2.5% of the world’s population. One of the therapeutic modalities for the treatment of moderate skin lesions is phototherapy with NB-UVB radiation (311 nm). The 290-315 nm UV radiation produces in the epidermis vitamin D of 7-dehydrocholesterol which is then hydroxylated into 25(OH)D and 1,25(OH)2D. Active metabolites of vitamin D, apart from regulating calcium-phosphorus homeostasis, have been shown to inhibit hyperproliferation and to induce terminal differentiation of cultured human keratinocytes through their action on the genome by the nuclear receptor VDR (vitamin D receptor). The literature includes many studies on VDR gene polymorphism and abnormal vitamin D metabolism in some patients with psoriasis. These anomalies could be possibly connected to adverse reactions to NB-UVB and treatment with vitamin D analogues.